Analysis and Modelling of The Sroyo Village Composite Bridge Superstructure Based on SNI 1725:2016 - Bryan Septian Ari Pratama; Annisa' Carina; Donny July Prasetyo (Universitas Islam Raden Rahmat, Malang, 2026)
This study aims to analyze, model and validate the superstructure of the Sroyo Village Composite Bridge to evaluate it structural safety while validating the manual calculating against computer-based modelling. The research method used is manual calculation analysis and computer-based structural modelling with SAP2000, in accordance with SNI 1725: 2016, RSNI T-03-2005 and SNI 2847: 2019. The results of the analysis show an ultimate moment of 991.25 kNm and an ultimate shear force of 304.60 kNm. This value is below the nominal moment capacity of 1365.57 kNm and nominal shear capacity of 648.00 kNm. The highest demand capacity ratio (DCR) is found in the shear connector at 0.98, while other internal force components can maintain safety control with a value of <1.00. The deflection that occurs is 12.36 mm which meets the allowable limit of 15.00 mm. Furthermore, validation of the results of manual analysis and SAP2000 modeling shows a minimum deviation of 0.07% and a maximum deviation of only 4.54% thus indicating the validity of the calculation results. Therefore, the superstructure of the Sroyo Village Composite Bridge is declared to meet structural feasibility according to Indonesian National Standards. However, this study is limited to the superstructure analysis.